Estética de un rostro en la era digital: viaje de la vanidad a la esencia real - Salazar-Gamarra, Rodrigo (2024)
We live in a world where digitalization has penetrated deep into almost every aspect of our routine life. Digital technologies, like facial scanning systems, computed tomography, and intraoral scanning systems, have been a revolution in dental and facial aesthetic, and it has been just as it is in most other fields (1). However, no matter how convenient the technical progress and precision in diagnosis largely become, they don't cover all that in a basic way lies behind the problems of mere outer vanity—the unconscious body image (2), intrinsic meaning of the face, and, thus, identity of an individual.